Diseño y análisis de un nuevo DAMS para reforzar las propiedades sismo resistente de estructuras con un comportamiento Elasto-Plástico - Riofrio Núñez, Alexander Raúl (2018)
To reduce vibrations during a seismic event, it was proposed to design a new tuned mass damper (TMD) that incorporates an element that provides negative rigidity and therefore reinforce the dynamic properties of structures with an elastic-plastic behavior. The methodology was to consider two systems that exhibit elasto-plastic behavior, a system (soil-structure) without protection and a system (soil-structure-TMD) with protection, subject them to seismic excitation, compare the responses of the systems (displacements in the base) and determine the effectiveness of the TMD to reduce displacements at the base of the structure. By using an element that contributes negative rigidity, it was possible to obtain a TMD with greater efficiency in reducing the displacements of the structure compared to previous investigations. The TMD behaves better in steel structures and that are on soft soils.